Playing with Fire: Narrating Angry Women and Men in the Heptaméron - Thompson, Emily E. (Renaissance and Reformation / Renaissance et Réforme, 2015)
In De Ira, Seneca dedicates three books to the denunciation of anger, a passion he insists serves no necessary purpose and leads to countless ills. Certainly Marguerite de Navarre acknowledges the violent potential of this passion in the stories of the Heptaméron. Yet her devisants not only justify some forms of anger in the stories they tell, they also freely give expression to their own anger during the ensuing discussions. The historian Natalie Zemon Davis even cites the Heptaméron as an example of a literary text that allows sixteenth century readers to imagine a menacing, yet justifiable female anger. A systematic study of references to anger in the Heptaméron indeed reveals a gendered revision of Seneca’s and Aristotle’s ideas on anger. Women with a distinctly feminine honour to defend take their place beside angry male warriors. And women are depicted as capable both of expressing anger and of controlling it. Marguerite’s choice of words, her sequencings of stories, and the arguments she expresses through her devisants suggest ways in which anger can be useful to both sexes. A necessary outlet for intense feeling, a controlled anger can balance a sense of noble self-affirmation with the self-abnegation required for social harmony and Christian salvation.